Tingkat Indeks Kepuasan Masyarakat Terhadap Kualitas Pelayanan Publik Surat Keterangan Catatan Kepolisian (SKCK) Di Polres Payakumbuh - Ario Harisman; Khairul Khairul (STIE AMKOP, 2023)
This research employed a quantitative descriptive method to obtain a true picture of the assessment of the performance of the Public Service for Police Record Certificate (SKCK) at Polres Payakumbuh. The objective of this study was to understand and determine the level of community satisfaction with the SKCK services in the Polres Payakumbuh area. The population of this study was the individuals who utilized the SKCK services at Polres Payakumbuh, totaling 100 respondents. A sample of 50 respondents was taken from the population using simple random sampling technique. Data collected from the survey on community satisfaction with the SKCK services at Polres Payakumbuh were analyzed using the SPSS (Statistical Package for the Social Sciences) software. The SPSS facilitated the data analysis process by providing comprehensive statistical features. Based on the analysis, it can be concluded that the community's level of satisfaction with the quality of public service for the SKCK at Polres Payakumbuh obtained a performance index value of 81.18, falling under the category of